STUDENTS' SELF-EVALUATION IN THE CONTEXT OF PRACTICAL PEDAGOGICAL TRAINING - Kolar, Danijela Rus (PEOPLE: International Journal of Social Sciences, 2018)
In this article we investigated the students’ self-evaluation in the context of practical pedagogical training in pedagogical second cycle study programmes at the Faculty of Natural Sciences and Mathematics, Faculty of Arts and Faculty of Education at the University of Maribor. The key research objectives were to determine how frequent the interviewed students performed self-evaluation of particular activities and, furthermore, self-evaluation of which activities students carried out the most during their practical training. 148 students participated in the research, namely 127 first year students and 21 second year students of second cycle study programmes at the previously mentioned faculties. The research results point out that less than 40 % of the interviewed students regularly self-evaluated particular activities during their practical training and that they used a highly varying number of hours for this purpose. Also, the results show a partly positive situation regarding the total performance of self-evaluation as well as regarding self-evaluation of particular activities. We believe that standardisation considering duration and scope of the students’ self-evaluation would lead to an improved performance of practical pedagogical training.